That's what friends are for - Rouse, Wade (MIRA, 2026)
"Theodore Copeland has created a fabulous life in the desert oasis of Palm Springs, where he shares a fabulous pink mid-century home with three fabulous friends: Barry, a former actor still clinging to his youth, his hair, and the memory of the dream role that killed his career; Ron, an uprooted Christian from the Midwest with a big heart but no one to give it to; Sid, who, after coming out late in life, has never found love. Teddy is the caustic, unspoken leader of "The Golden Gays"--the foursome's monthly drag tribute to The Golden Girls. Despite their foibles and bickering, they have turned their golden years into a golden era. But the harmony of their desert enclave becomes a carousel of emotional baggage when Teddy's estranged sister, Trudy, shows up on their doorstep, her dramatic teenage granddaughter in tow. While Teddy keeps Trudy at arm's length, she manages to wheedle her way into the lives of the Golden Gays, until the real reason for her visit is revealed and the secrets they've all been keeping from each other unravel faster than a hastily stitched hemline."--Amazon.